The letters to Timothy and Titus - Towner, Philip H., 1953- (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2006)
The most accessible, most broadly pitched full-length commentary on Timothy and Titus, this NICNT volume explores Paul's three letters to Timothy and Titus within their historical, religious, and cultural settings. In his introduction, Towner sets out the rationale for his historical approach, questions certain assumptions of recent critical scholarship, and establishes the uniqueness and individuality of each letter. Significantly, Towner's work displays unprecedented interaction with four recent major commentaries on these Pauline letters. Centered on an outstanding translation of the Greek text and including thorough footnotes, bibliographical citations, and indexes, Towner's commentary on Timothy and Titus is sure to become a standard reference for busy pastors, students, and scholars.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries